Understanding the need for novelty from the perspective of self-determination theory. (November 2016) - González-Cutre, David; Sicilia, Álvaro; Sierra, Ana C.; Ferriz, Roberto; Hagger, Martin S.
Abstract: A fundamental tenet of self-determination theory is that the satisfaction of three basic, innate psychological needs for autonomy, competence, and relatedness is necessary for optimal functioning. The aim of this research was to propose novelty as a basic psychological need in self-determination theory and develop a new measure to assess novelty need satisfaction, the Novelty Need Satisfaction Scale (NNSS). Two studies were performed, one at the global lifestyle level (Study 1: general adults, N  = 399, M age  = 31.30 years) and the other at a contextual level in physical education (Study 2: first-year post-compulsory secondary school students, N  = 1035, M age  = 16.20 years). Participants completed the NNSS alongside measures of psychological needs and regulation styles from self-determination theory and psychological well-being. The six-item NNSS showed adequate psychometric properties and discriminant validity with other psychological needs in both studies. Novelty need satisfaction predicted life satisfaction (Study 1) and intrinsic motivation in physical education (Study 2) independent of the other three psychological needs. Results provide preliminary evidence that need for novelty is a unique candidate need alongside existing needs from self-determination theory, but further confirmatory and experimental research is required. Highlights: A measure of the satisfaction of the need for novelty was developed. Satisfaction of the need for novelty predicted life satisfaction. Satisfaction of the need for novelty in physical education was related to autonomous motivation. Results provide preliminary evidence that need for novelty is a unique candidate need, but further research is required.